Observations Regarding the Lime Stucco Ornaments of the Safavid and Qajar Baths in Iran's Kurdistan Province - Derakhshesh, Tayebeh Hosseinpour; Shiran, Habib Shahbazi; Zarei, Mohamad Ebrahim; Hajizadeh, Karim (Journal of Islamic Architecture, 2025)
In addition to furnishing insights into their aesthetic aspects, inquiry into the architectural ornaments of public buildings reveals the interests of their commissioners and the public. Lime stuccowork assumed a central place among the architectural ornaments of bathhouses due to lime’s workability and its use as a major resilient building material in such hot and humid atmospheres. The present study seeks to investigate and analyze the lime stucco ornaments at bathhouses of Kurdistan Province in the timeframe spanning the Safavid to the end of the Qajar period. This descriptive, historical-comparative research builds on both field and library research to explore the lime stuccoworks at the bathhouses of the province. Research questions tackled here include: (1) What were the themes of the main lime stucco ornaments, and what role did the local rulers play in their creation? (2) Where did these decorative elements take inspiration from? The results of the research show that the employed decorative patterns consist of geometric, Islimi, vegetal, flower, vase, and animal and bird ornaments. These decorative elements drew inspiration from nature, ancient beliefs, and archaism. In fact, local rulers and commissioners were responsible for the flourishing and spread of this art. Due to their influence in the coeval political and administrative institutions, they managed to hire skilled craftsmen from the capital or regions abroad to construct such constructions that, beside invoking those popularly used in the region, benefited from a series of indigenous ornamental patterns.